Diálogos entre a justiça restaurativa e a justiça social pela via de acesso a direitos e seus reflexos sobre adolescentes em conflito com a lei - Natália de Souza Neves (2021)
This research aimed at understanding the possibilities and limits of a restorative justice approach that incorporates social justice to be applied in the juvenile justice system, with adolescents who commit offenses in Brazil. For such purpose, it first offers a theoretical analysis of the doctrine of integral protection, which guides the treatment of children and adolescents nowadays in the country. According to this doctrine, children and adolescents – who are in a peculiar condition of development in their lives – possess specific rights. Indeed, they are entitled to a catalogue of rights, in addition to other guarantees, due to that peculiar condition. When adolescents commit any offence, they are granted procedural guarantees during the legal process. In addition, during their process of accountability they enjoy a range of individual and social rights, and socioeducation is a vector that guides the application of a socioeducational sanction. Secondly, in order to expand the lenses on how to deal with adolescents who commit offenses, prioritizing a more humanized treatment and reparation over punishment, the foundations of restorative justice were analyzed. This new form of justice represents a paradigm shift in the treatment of crimes and infractions, by proposing a change of focus from legal transgression to the damage caused by the occurrence of an offence, seeking the reparation of the victims and the restoration of stakeholders directly involved in the context of the offence, including victims, community and offender, as well as the relations between them. The obligations and needs that arise when harm is done, the individual and collective accountability and the engagement of stakeholders are important pillars of restorative justice, which should be considered in the application of the different formats of restorative practices. Thirdly, aiming to establish a relation between restorative justice and social justice, I analyzed the capability approach developed by Amartya Sen. According to Sen, when evaluating social justice in a specific society one should consider freedom, capacities and the real opportunities of people who live in such society, as well as the life they lead, according to the objectives they have set for themselves. Based on the capability approach, and considering the aim of restorative justice to address the needs of the stakeholders that arise and underlie the occurrence of crimes and infractions, I aimed at emphasizing the importance of a restorative justice approach that incorporates social justice. Finally, it was concluded, through the analyses of the doctrine of integral protection, and of the theoretical framework of restorative justice, that there is a theoretical and methodological basis for a restorative justice approach that incorporates social justice to be applied with adolescents who commit offenses in Brazil. Such approach becomes possible through the increase in access to human rights, accomplished by the direct and indirect participation in restorative practices of representatives of the Child and Adolescent Rights Guarantee System. The widespread application of this approach has the potential of qualifying the judicial experience undergone by the stakeholders during restorative practices. Such approach is valued in contexts characterized by high rates of crime, violence and abyssal social inequalities, as the ones prevalent in Brazil.